Meningkatkan Kualitas Produk UMKM Makanan Untuk Meningkatkan Peminat Konsumen dan Melakukan Pemasaran Digital di Kabupaten Solok-Selatan - Yunita, Ermai; Annas, Firdaus; Putri, Aimala (Yayasan Lembaga Studi Makwa, 2023)
Micro, small and medium enterprises (MSMEs) have a strategic role in driving economic growth, especially in South Solok Regency. However, the main challenges faced are improving product quality in order to attract consumer interest and utilizing digital marketing effectively. This article discusses strategic efforts to improve the quality of MSME products through innovation and standardization, as well as the application of digital marketing strategies to expand market reach. The methods used include market needs analysis, product quality training, and implementation of technology-based digital marketing. The results show that improving product quality not only improves the competitiveness of MSMEs, but also attracts the attention of local and global consumers. In addition, the utilization of digital marketing is proven to strengthen brand awareness and expand market access. The development of MSMEs in South Solok Regency requires a holistic approach that includes improving product quality and optimizing digital marketing. Superior product quality is key in meeting consumer expectations while creating a competitive advantage. Meanwhile, digital marketing offers great opportunities to reach a wider market and is cost-efficient. By utilizing digital platforms such as social media, e-commerce, and search engine optimization strategies, MSMEs can introduce products more effectively to potential customers. The combination of product innovation and strategic digital marketing not only increases sales, but also strengthens the brand identity of MSMEs in an increasingly competitive market. Improving product quality is an important factor in supporting the development of Micro, Small and Medium Enterprises (MSMEs), especially in South Solok Regency. This article discusses strategies that can be applied to improve the quality of MSME products so that they can attract consumers more effectively. In addition, the discussion also focuses on the application of digital marketing as a step to expand market reach and improve the competitiveness of MSMEs in the current technological era. This research uses the Research and Development (R&D) method which involves product development through the process of needs analysis, design, testing, and evaluation.